A design of an all-MOS-transistor low-power low-voltage LDO with an embedded voltage reference - Chua, Xin Xue (2019)
This report shows the design of Low Dropout (LDO) Voltage Regulator with an embedded voltage reference, which provides a certain output voltage independent of supply voltage, temperature and loading current. Three design has been done in this report starting from the poorest performance design to the best performance design. The final design is using a start-up circuit, embedded voltage reference, error amplifier and a temperature curvature correction circuit. The final design is not using any resistors.